PECULIARITIES OF SUBJECTIVE WELL-BEING IN THE INTENTION OF YOUNG PEOPLE TO MIGRATE - Mkrtchyan , A. A. (Modern Psychology, 2018)
The article examines the role of separate components of subjective well-being and the intentions of the young people to migrate, in particular the analysis of an emotional, social and psychological peculiarities of well-being among the young adults from Yerevan. A comprehensive study of subjective well-being enables us to understand the motives behind the behavioral manifestations of a person. The results of the survey show that young people intending to leave Armenia have a lower degree of social well-being (social integration, acceptance and social realization) than those who do not have such an intention. The results of the research are the basis for the development of strategies for the prevention of the problem.
Keywords: subjective, psychological, social, well-being, eudaimonia, migration, intentions.